The effect of bi-functionalized MMT on morphology, thermal stability, dynamic mechanical, and tensile properties of epoxy/organoclay nanocomposites - Chee, Siew Sand; Jawaid, Mohammad (MDPI, 2019)
In this work, the optimum filler loading to prepare epoxy/organoclay nanocomposites by the in-situ polymerization method was studied. Bi-functionalized montmorillonite at different filler loading (0.5, 1.0, 2.0, 4.0 wt %) was dispersed in epoxy resin by using a high shear speed homogenizer. The effect on morphology, thermal, dynamic mechanical, and tensile properties of the epoxy/organoclay nanocomposites were studied in this work. Wide-angle X-ray scattering (WAXS) and field emission scanning electron microscope (FESEM) studies revealed that possible intercalated structures were obtained in epoxy/organoclay nanocomposites. Thermogravimetric analysis (TGA) shows that epoxy/organoclay nanocomposites exhibit higher thermal stability at the maximum and final decomposition temperature, as well as higher char content, compared to pristine epoxy. The dynamic mechanical analysis (DMA) indicate that storage modulus (E′), loss modulus (E″), cross-link density and glass transition temperature (Tg) of the nanocomposites were improved with organoclay loading up to 1 wt %. Beyond this loading limit, the deterioration of properties was observed. A similar trend was also observed on tensile strength and modulus. We concluded from this study that organoclay loading up to 1 wt % is suitable for further study to fabricate hybrid nanocomposites for various applications.